Human Resource Planning and Recruitment Management in Islamic Educational Institutions: A Case Study of HR Strategy and Processes - Fardan Abdul Basith; Muhammad Ridwan Aziz; Ayi Dini Purwandi; Dwi Haryanto Hamdani; Badrudin Badrudin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Human resource management (HRM) is a crucial component in strengthening the quality and sustainability of Islamic educational institutions, including Boarding schools. As educational demands increasingly require professionalism, digital competence, and organizational effectiveness, Boarding schools must manage their human resources through systematic planning and recruitment. This study explores HR planning and recruitment at Boarding School Al-Musyarrofah, Cianjur, focusing on how workforce needs are identified, how future HR demands are forecasted, and how recruitment strategies align with institutional goals and Islamic educational values. Using a qualitative case study approach, data were collected through interviews, observations, and documentation to analyze HR practices and challenges within the Boarding School context. The study is guided by several research questions: how the Boarding School conducts HR planning, how it forecasts future workforce requirements, what recruitment strategies are employed, how Islamic values influence HR processes, and what obstacles arise in implementation. The theoretical framework integrates modern HRM theories such as workforce planning, competency-based recruitment, and structured selection processes with principles of Islamic education emphasizing amanah, adab, khidmah, and educator integrity. This hybrid framework positions HRM not only as a managerial function but also as a moral responsibility. The study contributes by offering an empirical model of HR planning and recruitment suited to Boarding schools, demonstrating how modern HRM principles can be harmonized with Islamic educational philosophy to produce effective, ethical, and culturally grounded HR practices.